Implementation of Problem Based Learning Model to Improve Student Learning Activities: Classroom Action Research at MIS Sumber Mas Ganding Sumenep - Rosyida, Vina Nur; Khasanah, Uswatun; Rahmawati, Wahidah; Fitrianingsih, Uun; Hasanah, Uswatun (Indonesian Journal of Education and Social Humanities, 2024)
This study aims to enhance student learning activities through the implementation of the Problem-Based Learning (PBL) model and to explore its practical application in elementary school classrooms. The research was conducted as a Classroom Action Research (CAR) at MIS Sumber Mas Ganding, Sumenep, involving fifth-grade students and focusing on the sub-theme "Diversity of Living Things in My Environment." The study was carried out over two cycles, each consisting of two face-to-face learning sessions. The four stages of CAR planning, implementation, observation, and reflection were used systematically to monitor and evaluate the process and outcomes. Data collection methods included observation, interviews, and documentation, ensuring a comprehensive understanding of the students’ learning activities and engagement. In the first cycle, the percentage of students actively participating in the learning process reached 61%, indicating the need for further improvement. After reflecting on the initial cycle and making necessary adjustments to the learning strategies, the second cycle was implemented. In this cycle, student learning activities increased significantly, reaching 81%, demonstrating a marked improvement in engagement and active participation. The findings suggest that the PBL model is effective in promoting student-centered learning, enhancing critical thinking skills, and encouraging active involvement in classroom activities. By presenting real-life problems and allowing students to collaborate in solving them, the PBL approach creates a more dynamic and meaningful learning experience. These results support the integration of PBL into elementary education as a strategy to improve both the quality of learning and student motivation.